Mechanical Properties of Conducting Printed Nanosheet Network Thin Films Under Uniaxial Compression - Coleman, Jonathan; Cross, Graham; Moebius, Matthias (My University, 2023)
Thin film networks of solution processed nanosheets show remarkable promise for use in a broad range of applications including strain sensors, energy storage, printed devices, textile electronics, and more. While it is known that their electronic properties rely heavily on their morphology, little is known of their mechanical nature, a glaring omission given the effect mechanical deformation has on the morphology of porous systems and the promise of mechanical post processing for tailored properties. Here, this work employs a recent advance in thin film mechanical testing called the Layer Compression Test to perform the first in situ analysis of printed nanosheet network compression. Due to the well-defined deformation geometry of this unique test, this work is able to explore the out-of-plane elastic, plastic, and creep deformation in these systems, extracting properties of elastic modulus, plastic yield, viscoelasticity, tensile failure and sheet bending vs. slippage under both out of plane uniaxial compression and tension. This work characterizes these for a range of networks of differing porosities and sheet sizgraphene and MoS2 networkses, for low and high compression, as well as the effect of chemical cross linking. This work explores graphene and MoS2 networks, from which the results can be extended to printed nanosheet networks as a whole
Keywords: printed graphene; nanosheets; porous systems; printed graphene; nanosheets; porous systems